Analysis of risk indicators for implant failure in patients with chronic periodontitis - Qiang Zhang; Sheng Guo; Yuan Li; Zhou Li; Deli Wang; Kai Zhang (BMC, 2024)
Abstract Dental implant restoration shows an effective method for the rehabilitation of missing teeth. The failure rate of periodontal implants in patients with chronic periodontitis is associated with periodontal flora, inflammation, and long-term periodontal bone resorption caused by chronic periodontitis. However, the therapeutic effects of dental implant restoration on inflammation in patients with chronic periodontitis have not addressed. The purpose of this study is to evaluate the risk indicators for inflammation, bone loss and implant failure in patients with chronic periodontitis. A total of 284 patients with dental implant restoration were recruited and divided into periodontally healthy patients (n = 128) and chronic periodontitis patients (n = 156). Periodontal indices including probing depth (PD), sulcus bleeding index (SBI), plaque index (PLI), gingival bleeding (GIL) and bleeding on probing (BOP) were compared in two groups. Inflammatory cytokines including tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleukin-1 (IL-1), matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9) levels at baseline, 6 and 12 months after surgery, and the implant survival rate at 12 months after surgery, as well as the risk factors associated with failure of dental implant were also assessed. Outcomes demonstrated that patients in the chronic periodontitis group had higher values of periodontal indices than those in the periodontally healthy group. All inflammatory parameters in the chronic periodontitis group were higher than those in the periodontally healthy group and negatively associated with the chronic periodontal index (CPI) in chronic periodontitis patients. Chronic periodontitis patients had higher the prevalence of mucositis and peri-implantitis than patients with healthy periodontium. Implant diameter, length and design was associated with the risk of implant failure for chronic periodontitis patients receiving dental implant. The cumulative implant failure rate and incidence of implant fractures for chronic periodontitis patients at 12 months after surgery were 12.10% and 7.23% (p < 0.05), respectively, while were lower in the heathy periodontitis patients. Location, diameter, implant design, immediate loading and bone defect were risk indicators for bone loss for dental implant patients. The risk factors associated with failure of dental implant was higher in chronic periodontitis patients than patients in the periodontally healthy group (14.25% vs. 4.92%, p < 0.05). In conclusion, data in the current study indicate that inflammation is a risk indicator bone loss, implant fracture and implant failure in patients with chronic periodontitis.